Incunabula Project blog : Cambridge University Library - Cambridge University Library (2010)
[Dt.:] Der Web log des Incunabula Project der Universitätsbibliothek Cambridge informiert über die Fortschritte bei der Katalogisierung von über 4650 Inkunabeln in der dortigen Sammlung sowie über einzelne Werke. - [Engl.:] The blog of the Incunabula Project of the Cambridge University Library provides information about the progress of the cataloging of the more than 4650 incunabulas in their collection as well as about individual works.